Manipulation of Nursing Faculty by Nursing Students - Strickland, Kasey Lynn (My University, 2013)
Manipulation in nursing education has not been widely studied; however, the concepts of incivility and entitlement have been extensively researched and reported within the context of nursing education. All three concepts have descriptors in common, providing a foundation for the exploration of manipulation in this educational setting. While manipulation has not been studied extensively in nursing education settings, it has been researched and discussed in clinical nursing literature and in forensic nursing literature. Manipulation has been noted to have characteristics similar to incivility discussed in nursing education literature. The Strickland Nursing Faculty Survey on Manipulation (SNFSM) was used to measure the experience of manipulation in nursing education. The SNFSM was sent electronically, with a link to Survey MonkeyrM to 148 nursing faculty members in 10 counties in the southern United States. Eighty nursing faculty members responded to the survey. Results of the survey indicate that nursing faculty experience manipulation in a variety of settings including but not limited to meetings with students, in person afterhours, and during test debriefing. Nursing faculty reported gossiping, twisting facts, lying, undermining authority, and defiance as manipulative characteristics observed in nursing students. The most common motivation attributed by faculty for student manipulation is the avoidance of accepting responsibility. Recommendations from this study beyond development of the instrumentation, include replicating this study in other settings and populations of nurse faculty, and include students in the study of their perceptions of manipulation in nursing academic settings.
Kasey L. Strickland Thesis 2013 -- Valdosta State University -- Nursing
Keywords: Nursing education; Nursing -- United States -- South; Strickland Nursing Faculty Survey on Manipulation; SNFSM; Nursing ethics; Nursing students -- attitudes